Gene polymorphisms of NOD2, IL23R, PTPN2 and ATG16L1 in patients with Crohn’s disease: on the way to personalized medicine? - Hoffmann, Peter; Lamerz, David; Hill, Petra; Kirchner, Marietta; Gauss, Annika (Genes, 2021)
Genetic and environmental factors are involved in the pathogenesis of inflammatory bowel diseases (IBD). The study aimed at investigating the potential influence of single nucleotide polymorphisms (SNPs) NOD2 rs2066844, NOD2 rs2066845, NOD2 rs2066847, IL23R rs11209026, PTPN2 rs2542151, PTPN2 rs7234029, and ATG16L1 rs2241880 on the response to immunomodulatory therapies and disease course in Crohn’s disease (CD). This is an uncontrolled retrospective monocentric study including patients from the IBD outpatient clinic of Heidelberg University Hospital. Therapy responses and disease courses were related to genetic findings. 379 patients with CD were included. The presence of at least one PTPN2 rs7234029 risk allele was associated with nonresponse to anti-interleukin-12/23 treatment (89.9% vs. 67.6%, p = 0.005). The NOD2 rs2066844 risk allele was associated with a first-degree family history of colon cancer (12.7% vs. 4.7%, p = 0.02), the ATG16L1 rs2241880 risk allele with ileal CD manifestation (p = 0.027), and the IL23R rs11209026 risk allele with a higher rate of CD-related surgeries per disease year (0.08 vs. 0.02, p = 0.025). The results of this study underline the relevance of genetic influences in CD. The association of the PTPN2 rs7234029 risk allele with nonresponse to anti-interleukin-12/23 treatment in CD patients is a novel finding and requires further investigation.